Newly Identified Au-Ag-Bi-Te Mineralization in the Aydindere Skarn Fe and Cu Deposit, Giresun, NE Turkey: Implications of Gold Mineralization during Retrograde Skarn Evolution - Sasmaz, Ahmet; Sukach, Vitaliy; Bondarenko, Serhiy; Aleksiienko, Hryhorii; Kaseb, Hengameh Erfanian; Sasmaz, Bilge; Voudouris, Panagiotis (China Univ Geosciences, Wuhan, 2025)
This study investigates the mineralogy and mineral-chemistry of a newly discovered Au-Ag-Bi-Te mineralization at the Aydindere Fe-Cu skarn deposit, within the Pontides Tectonic Unit, northeastern Turkey. The mineralization is developed in the skarn zone at the contact between Upper Cretaceous andesite-pyroclastic rocks and a Paleocene-Eocene I-type granitoid. The principal ore minerals of the Aydindere Fe-Cu deposit are oxides (magnetite), sulfides (pyrite-chalcopyrite-galena-sphalerite), tellurides/sulfotellurides (tetradymite, hessite), sulfosalts (wittichenite, emplectite, aikinite) and native gold-electrum. Skarn minerals include anhydrous phases (garnet) formed in a prograde stage and hydrous phases (amphibole, epidote, chlorite), which were formed in a retrograde stage in association with quartz, adularia, apatite and late calcite. Sulfides, tellurides and sulfosalts are introduced during the retrograde stage. The Au-Ag-Bi-Te mineralization was detected for the first time within the western ore body of the Aydindere deposit, and occurs in calcite-bearing sulfide bodies that cut magnetite-garnet-amphibole-epidote skarns with magnetite ores of different grade, including massive magnetite. Chlorite geothermometry indicates formation of the Au-Ag-Bi-Te mineralization at temperatures between 300 and 250 degrees C, during the retrograde skarn evolution. Assuming the temperature is similar to 275 degrees C, logfS2 = -10.5 to -13, logfO2 = -37 to -33, and logfTe2 values range from approximately -12 to -8.5 were estimated. The available mineralogical and geological data (presences of magnetite, oxidized-type tellurides/sulfotellurides, and andraditic garnets, and absence of pyrrhotite and arsenopyrite) suggest that Aydindere is an oxidized Au-bearing skarn deposit. The discovery of Au-Ag-Bi-Te mineralization at Aydindere increases its productivity and requires more detailed exploration in the deposit for precious (Au, Ag) and critical (Bi, Te) metals.
Keywords: aydindere; Black Sea Region; telluredes; oxidized gold-bearing skarn deposit; mineral geology